In vitro study of the inflammatory cells response to biodegradable Mg-based alloy extract - Jin, Liang; Wu, Jing; Yuan, Guangyin; Chen, Tongxin (PLOS ONE, 2018)
Biodegradable Mg-based alloys have shown great potential as bone fixation devices or vascular stents. As implant biomaterials, the foreign body reaction (FBR) is an important issue to be studied, where the inflammatory cells play a key role. Here, we used two inflammatory cell lines i.e. THP-1 cells and THP-1 macrophages, to evaluate the effect of Mg–Nd–Zn–Zr alloy (denoted as JDBM) extracts on cell viability, death modes, cell cycle, phagocytosis, differentiation, migration and inflammatory response. The results showed that high-concentration extract induced necrosis and complete damage of cell function. For middle-concentration extract, cell apoptosis and partially impaired cell function were observed. TNF-α expression of macrophages was up-regulated by co-culture with extract in 20% concentration, but was down-regulated in the same concentration in the presence of LPS stimulation. Interestingly, the production of TNF-α decreased when macrophages were cultured in middle and high concentration extracts independent of LPS. Cell viability was also negatively affected by magnesium ions in JDBM extracts, which was a potential factor affecting cell function. Our results provide new information about the impact of Mg alloy extracts on phenotype of immune cells and the potential mechanism, which should be taken into account prior to clinical applications.